Investigating the association between diabetes and mental health: A train-and-test approach - Kang, Weixi (Frontiers in Psychiatry, 2022)
Diabetes is a chronic health condition that affects how the body turns food into energy. Research has demonstrated a relationship between diabetes and various mental health issues, which include psychiatric disorders and other problems that are specific for people living with diabetes. Although previous studies have shed light on the associations between diabetes and various types of mental health issues with a focus on depression & anxiety, much less is known about how diabetes is associated with other dimensions of mental health such as social dysfunction & anhedonia and loss of confidence in a large nationally representative survey from the United Kingdom. The aim of the current study is to replicate the factor structure of the GHQ-12 and investigate how diabetes is related to general mental health and dimensions of mental health. By adopting a train-and-test approach to data from the UKHLS including 2, 255 diabetes patients and 14, 585 participants who indicated that they were not clinically diagnosed with diabetes, the current found that hypotheses are well-supported by the results.